Blackfoot Ways of Knowing The Worldview of the Siksikaitsitapi - Bastien, Betty (University of Calgary Press, 2004)
Blackfoot Ways of Knowing is a journey into the heart and soul of Blackfoot culture. In sharing her personal story of "coming home" to reclaim her identity within that culture, Betty Bastien offers us a gateway into traditional Blackfoot ways of understanding and experiencing the world. As a scholar and researcher, Bastien is also able to place Blackfoot tradition within the context of knowledge building among indigenous peoples generally, and within a historical context of precarious survival amid colonial displacement and cultural genocide. In mapping her own process of coming to know, Bastien stresses the recovery of the Blackfoot language and of the Blackfoot notions of reciprocal responsibilities and interdependence. For the Siksikaitsitapi, knowledge is experiential, participatory, and ultimately sacred, rather than objective and inert. Rekindling traditional ways of knowing is essential if First Nations people in Canada are to heal and rebuild their communities and cultures. By sharing what she has learned, Betty Bastien hopes to ensure that the next generation of First Nations people will enjoy a future of hope and peace.